Combining Lattice Boltzmann method and genetic algorithm to optimize the layout of artificial floating islands in river network in China - Bai, Yu; Xiao, Yizhou; Qi, Yiting; Qian, Jinglin; Xuan, Weidong; Pan, Suli; Sun, Guojin (Environmental science and pollution research international, 2023)
How to solve the pollution problem of water environment in river network is a hot issue in the world. Artificial floating island is an efficient way to deal with water pollution. Taking Jiashan, Zhejiang, China, as an example, Lattice Boltzmann method (LBM) is used to simulate the law of hydrodynamics and pollutant transport in river network. Lattice Boltzmann equations are established in both artificial floating island and non-artificial floating island sections, and the river network boundary is automatically identified. The simulation results have high accuracy and are more suitable for the establishment of complex boundaries. On this basis, combined with the genetic algorithm (GA) module, the location of the artificial floating island is optimized, and the retention ratio of the pollution in optimized layout of artificial floating island is between and 2.4 and 7.2%. The research results of this paper can provide theoretical reference for the selection and location of artificial floating island in practical engineering.